Hubungan antara Keaktifan Ekstrakurikuler Rohani Islam (Rohis) dengan Minat Belajar PAI pada Peserta Didik Kelas XI di SMA Dwiwarna (Boarding School) Parung Bogor - Dalillah, Assyifa; Nurul, Sri; Sutisna (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this research namely: (1) to find out the level of rohis activity in class XI students at SMA Dwiwarna (Boarding School) Parung Bogor, (2) to find out the interest in learning PAI in class XI students at SMA Dwiwarna (Boarding School) Parung Bogor, (3) to determine the relationship between rohis activity and interest in learning PAI in class XI students at SMA Dwiwarna (Boarding School) Parung Bogor. The data collection technique used was a survey by distributing questionnaires to 57 class XI students, for data analysis namely scoring, normality test and linearity test and the method used was correlation. The results of this study indicate that: (1) rohis activity is included in the moderate category, (2) interest in learning PAI is included in the moderate category, (3) there is a positive and significant relationship between rohis activity and interest in learning PAI which is included in the category moderate or sufficient